(untitled) (Al-Mansour Journal, 2022)
The objective of this research is to identify the level of services provided for religious tourists, who visit the provinces of Karbala and Najaf during the year. By providing them the appropriate hotels, and the level of quality services offered by these hotels .Also the ratio of expenses and revenues and the ratio operators incurred by hotels in the two governorates to serve guests. In order to upgrade these services to attract more visitors, and provide services meet the needs and the expectations of visitors, and make them satisfy. That increases the national income of the country, and provides opportunities jobs for a large segment of unemployed. This research had adopted the (comparative) analytical approach, included numbers of 602 and 247 hotels and motels (residential complex shelter) in Karbala and Najaf respectively. The most important results of this research are: *the services provided by the private sectors hotels in general are not very good, expect the internet services which gives the highest level of services. *the ratio of hotels’ operators in Najaf is more than the ratio of hotels’ operators in Karbala ,so this increases the ratio of labor cost in Karbala more four times the ratio of labor cost in Najaf.